Mamluk History through Architecture: Monuments, Culture, and Politics in Medieval Egypt and Syria By Nasser Rabbat (London: I.B. Tauris, 2010. 261 pages.) (American Journal of Islam and Society, 2012)
This exhaustive series of fifteen essays, all produced by the author during1989-2005, covers many relevant facets of the Mamluk slave dynasty (1250–1517). By collecting these previously published essays in a single volume, atrajectory of interpretation can be contextualized and understood. Nasser Rabbat,a key figure in the contemporary study of Islamic architecture, is directorof the Aga Khan Program for Islamic Architecture at MIT. The essays, organizedinto four thematic parts, begin with a conceptual understanding of the Mamluks and their role and then look at their architecture through the lensesof history, language, and cultural index ...